A Chromosome-length Assembly of the Black Petaltail (Tanypteryx hageni) Dragonfly. (18th February 2023) - Tolman, Ethan R; Beatty, Christopher D; Bush, Jonas; Kohli, Manpreet; Moreno, Carlos M; Ware, Jessica L; Weber, K Scott; Khan, Ruqayya; Maheshwari, Chirag; Weisz, David; Dudchenko, Olga; Aiden, Erez Lieberman; et al.
Abstract: We present a chromosome-length genome assembly and annotation of the Black Petaltail dragonfly ( Tanypteryx hageni ). This habitat specialist diverged from its sister species over 70 million years ago, and separated from the most closely related Odonata with a reference genome 150 million years ago. Using PacBio HiFi reads and Hi-C data for scaffolding we produce one of the most high-quality Odonata genomes to date. A scaffold N50 of 206.6 Mb and a single copy BUSCO score of 96.2% indicate high contiguity and completeness.